PENGUNGKAPAN INFORMASI LINGKUNGAN SEBAGAI SARANA LEGITIMASI: STUDI EKSPERIMEN - , NITIA PRIYUSTINA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
The purpose of this study is to empirically examine the efectivity of disclosing soft disclosure environmental information, in order to save the reputation of a company whose environmental performance is not considered good. Soft disclosure information is information which is not related to the empirical environmental performance of the company, instead, it is related to mere claim or commitment that can be created even by a company with worst environmental performance. In other words, this study intended to examine whether certain environmental information can be used to make a fallacy into thinking a companyâs bad environmental performance as an acceptable one, or, in other words, legitimizing the bad environmental performance. This study is using experimental method. The experiment involves 91 undergraduate accounting students. The result suggests that, when investors get exactly same information about a company whose environmental performance is bad an operate in environmentally sensitive industry, there will be different investment decision between investors who get additional soft disclosure environmental information and those who do not.